Pengaruh Dosis Aluminium Sulfat Terhadap Kekeruhan dan Kadar Besi Air Baku pada IPA PDAM X - Simatupang , Dimas Frananta; Saragih , Gimelliya; Siahaan , Martin (Politeknik ATI Padang, 2021)
One of the first steps in processing river water into drinking water is by removing the turbidity of the river water. Turbidity can be removed by adding a chemical called a coagulant. This study aims to obtain data on how the effect of using coagulant dosage variations in reducing turbidity and iron content in raw water at the water treatment plant (IPA) PDAM X. The study was conducted using the jar test method to determine the dose of aluminum sulfate coagulant in reducing turbidity and colorimetric method using visible spectrophotometry to determine iron content that meets quality standard criteria. The results showed that the higher the coagulant dose, the lower the turbidity and iron content of the raw water. Coagulant doses with up to 30 ppm were able to reduce turbidity with an efficiency of 92.67% and reduce iron levels up 96.10%.